Nuclear receptor Nurr1 agonists enhance its dual functions and improve behavioral deficits in an animal model of Parkinson’s disease - Kim, Chun-Hyung (2015)
Parkinson’s disease (PD), primarily caused by selective degeneration of midbrain dopamine (mDA) neurons, is the most prevalent movement disorder, affecting 1–2% of the global population over the age of 65. Currently available pharmacological treatments are largely symptomatic and lose their efficacy over time with accompanying severe side effects such as dyskinesia. Thus, there is an unmet clinical need to develop mechanism-based and/or disease-modifying treatments. Based on the unique dual role of the nuclear orphan receptor Nurr1 for development and maintenance of mDA neurons and their protection from inflammation-induced death, we hypothesize that Nurr1 can be a molecular target for neuroprotective therapeutic development for PD. Here we show successful identification of Nurr1 agonists sharing an identical chemical scaffold, 4-amino-7-chloroquinoline, suggesting a critical structure–activity relationship. In particular, we found that two antimalarial drugs, amodiaquine and chloroquine stimulate the transcriptional function of Nurr1 through physical interaction with its ligand binding domain (LBD). Remarkably, these compounds were able to enhance the contrasting dual functions of Nurr1 by further increasing transcriptional activation of mDA-specific genes and further enhancing transrepression of neurotoxic proinflammatory gene expression in microglia. Importantly, these compounds significantly improved behavioral deficits in 6-hydroxydopamine lesioned rat model of PD without any detectable signs of dyskinesia-like behavior. These findings offer proof of principle that small molecules targeting the Nurr1 LBD can be used as a mechanism-based and neuroprotective strategy for PD.